Primary resistance to osimertinib due to SCLC transformation: Issue of T790M determination on liquid re-biopsy. (January 2018) - Minari, R.; Bordi, P.; Del Re, M.; Facchinetti, F.; Mazzoni, F.; Barbieri, F.; Camerini, A.; Comin, C.E.; Gnetti, L.; Azzoni, C.; Nizzoli, R.; Bortesi, B.; et al.
Highlights: Liquid biopsy alone could underestimate coexistence of resistance mechanisms. T790M plasma levels should be taken into account for clinical decisions. Low EGFR-T790M/activating mutation ratio may suggest tissue re-biopsy. p53 and Rb1 expression on diagnostic biopsy may predict SCLC transformation. Abstract: Objectives: EGFR T790M mutation is the most common mechanism of resistance to first-/second-generation EGFR tyrosine kinase inhibitors (TKIs) in non-small cell lung cancer (NSCLC) and could be overcome by third-generation EGFR-TKIs, such as osimertinib. Liquid biopsy, a non-invasive technique used to test the presence of the resistant mutation, may help avoiding tissue re-biopsy. However, analysing only circulating-free DNA, information about other less frequent and coexisting resistance mechanisms may remain unrevealed. Materials and methods: All patients reported in this series participated in the ASTRIS trial, a real world treatment study testing the efficacy of osimertinib (80 mg os die) in advanced T790M-positive NSCLC progressed to prior EGFR-TKI. Patients were considered eligible to osimertinib if T790M positive on tissue or plasma samples. In our patients, EGFR molecular testing on blood sample was conducted with digital droplet PCR (ddPCR). Results: We report our experience of five patients treated with osimertinib after T790M detection on liquid biopsy that presented a disease progression at first tumor assessment mediated by SCLC transformation, as evidenced at tissue re-biopsies. All patients showed low ratio T790M/activating mutation in the blood before osimertinib (lower than 0.03). For three patients, EGFR mutational analysis was T790M-negative when re-assessed by using a less sensitive method ( therascreen ® ) on the same liquid biopsy sample analysed by ddPCR before osimertinib therapy. Conclusion: Although liquid biopsy is a relevant tool to diagnose T790M presence in NSCLC patients resistant to EGFR-TKI, in case of a low ratio T790M/activating mutation, tissue biopsy should be considered to exclude the presence of SCLC transformation and/or other concomitant resistance mechanisms.